2007
DOI: 10.1021/tx600334x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism in Vitro and in Vivo of the DNA Base Adduct, M1G

Abstract: Oxidative damage is considered a major contributing factor to genetic diseases including cancer. Our laboratory is evaluating endogenously formed DNA adducts as genomic biomarkers of oxidative injury. Recent efforts have focused on investigating the metabolic stability of adducts in vitro and in vivo. Here, we demonstrate that the base adduct, M 1 G, undergoes oxidative metabolism in vitro in rat liver cytosol (RLC, K m ) 105 µM and V max /K m ) 0.005 min -1 mg -1 ) and in vivo when administered intravenously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 44 publications
3
23
0
Order By: Relevance
“…Purine-based therapeutics such as acyclovir, penciclovir, zaleplon, and others readily undergo oxidative metabolism and active transport (26)(27)(28)(29)(30)(31)(32)(33)(34). Our results on the oxidative metabolism of M 1 dG and M 1 G suggest that metabolism and alternate routes of elimination may also contribute to the complexity of DNA adduct analysis in biological matrixes (18,19).…”
Section: Discussionmentioning
confidence: 78%
“…Purine-based therapeutics such as acyclovir, penciclovir, zaleplon, and others readily undergo oxidative metabolism and active transport (26)(27)(28)(29)(30)(31)(32)(33)(34). Our results on the oxidative metabolism of M 1 dG and M 1 G suggest that metabolism and alternate routes of elimination may also contribute to the complexity of DNA adduct analysis in biological matrixes (18,19).…”
Section: Discussionmentioning
confidence: 78%
“…However, it would seem that most of these studies have examined the oxidation of 8-oxoGua in situ in DNA (84), rather than as a postexcision product of DNA repair, which may alter the likelihood of oxidation and its ''oxidizability.'' In contrast, M 1 G and 3-(2-deoxy-h-D-erythro-pentofuranosyl)pyrimido[1,2-a]purin-10(3H)-one both seem to undergo further oxidative metabolism in rat liver cytosol, with the base adduct being a better substrate for such enzymic oxidation than the deoxyribonucleoside adduct (85,86). There is also some evidence to suggest that M 1 G is further oxidized when given i.v., although 3-(2-deoxyh-D-erythro-pentofuranosyl)pyrimido[1,2-a]purin-10(3H)-one was not examined (85).…”
Section: Methods Of Analysismentioning
confidence: 99%
“…With M 1 dG, metabolic and pharmacokinetic studies in rats revealed a biphasic elimination from plasma with M 1 dG found in the urine for more than 24 hr after dosing 150. Analysis of urine revealed a metabolite of M 1 dG, 6-oxo-M 1 dG, likely derived from hepatic xanthine oxidase activity,150 with evidence for further oxidation of 6-oxo-M 1 dG on the imidazole ring to give 2,6-dioxo-M 1 G 151. Both of these studies raise the possibility that urinary biomarker studies may be underestimating the true level of adducts as a result of loss of the parent forms.…”
Section: Nucleic Acid Damage Products As Biomarkers Of Chronic Inflammentioning
confidence: 98%